Adaptive Resilient Control of Grid-Forming Converters for High-Renewable Transmission Networks - khalifa, Rio (Journal of Electrical Engineering, 2025)
High renewable penetration makes the transmission grid inertia-light and vulnerable to frequency/voltage deviations, interconverter resonances, and current limits during disturbances. This paper proposes an Adaptive-Resilient Grid-Forming Converter (AR-GFC) that integrates online grid strength estimation (eSCR), multi-scale tuning—slow-adaptation for virtual inertia/damping/droop and fastadaptation for impedance reshaping—as well as angle-aware current limiting and post-fault resynchronization. Stability verification is performed through passivity/sector-bounded certification and ISS Lyapunov, while multi-GFC coordination utilizes virtual Δf/ΔV sharing. EMT and HIL evaluations under SCR 6→1.7, load step, and FRT 1-φ/3-φ (120–200 ms) scenarios show that AR-GFC reduces ROCOF by ~35–40%, increases nadir frequency by +0.1–0.2 Hz, accelerates settling by 30–35%, and reduces voltage overshoot by 2530%. At FRT, current violations are limited to ≤20 ms around ≈100% without internal angle loss; phase margin increases by +20–25°, the 4–6 Hz resonance peak is eliminated, and power sharing errors shrink to |ΔP|, |ΔQ| ≈3–4% while reducing I²t by ~20% and curtailment by 12 18%. These results confirm that AR-GFC maintains robust and fault tolerant grid-forming properties, making it suitable for adoption in high renewable penetration transmission networks.